The Neurovascular Protective Effect of S14G‐Humanin in a Murine MCAO Model and Brain Endothelial Cells. Issue 7 (12th July 2018) - Peng, Tao; Wan, Wencui; Wang, Jingtao; Liu, Yu; Fu, Zhenqiang; Ma, Xingrong; Li, Junmin; Sun, Guifang; Ji, Yangfei; Lu, Jingjing; Lu, Hong; Liu, Yufeng
Abstract: Endothelial dysfunction is fundamental to ischemic stroke and brain injury. The humanin analogue S14G‐humanin (HNG) has been shown to be a cytoprotective derivative. In this study, we investigated the neuroprotective effects of HNG in vivo and in vitro . In a murine middle cerebral artery occlusion (MCAO) stroke model, HNG ameliorates cerebral infarction and suppresses the production of TNF‐α, IL‐1β, IL‐6 and MCP‐1 cytokines. HNG inhibits the expression of vascular adhesion molecules such as VCAM‐1 and ICAM‐1 in the cortex tissue. In mouse brain endothelial cells bEnd.3, HNG protects cell survival under oxygen deprivation (OGD) conditions. HNG suppresses ROS production as well as that of the same panel of cytokines and vascular adhesion molecules induced by OGD. HNG also reduces the numbers of THP‐1 cells attached to bEnd.3 by OGD. Mechanistically, we show that HNG exerts its effect via inhibition of the NF‐ κB pathway factor IKKα, activation of IκBα and accumulation of p65 in the nucleus. Our data conclude that S14G‐humanin serves as a neuroprotective factor, especially in brain vascular disorders. © 2018 IUBMB Life, 70(7):691–699, 2018